PHT427 as an effective New Delhi metallo-β-lactamase-1 (NDM-1) inhibitor restored the susceptibility of meropenem against Enterobacteriaceae producing NDM-1 - Li, Xiaohui; Wang, Qian; Zheng, Ji; Guan, Yan; Liu, Chennan; Han, Jiangxue; Liu, Sihan; Liu, Tianjun; Xiao, Chunling; Wang, Xiao; Liu, Yishuang (Frontiers in Microbiology, 2023)
Introduction With the increasingly serious problem of bacterial drug resistance caused by NDM-1, it is an important strategy to find effective inhibitors to assist β-lactam antibiotic treatment against NDM-1 resistant bacteria. In this study, PHT427 (4-dodecyl-N-1,3,4-thiadiazol-2-yl-benzenesulfonamide) was identified as a novel NDM-1 inhibitor and restored the susceptibility of meropenem against Enterobacteriaceae producing NDM-1. Methods We used a high throughput screening model to find NDM-1 inhibitor in the library of small molecular compounds. The interaction between the hit compound PHT427 and NDM-1 was analyzed by fluorescence quenching, surface plasmon resonance (SPR) assay, and molecular docking analysis. The efficacy of the compound in combination with meropenem was evaluated by determining the FICIs of Escherichia coli BL21(DE3)/pET30a(+)-blaNDM–1 and Klebsiella pneumoniae clinical strain C1928 (producing NDM-1). In addition, the mechanism of the inhibitory effect of PHT427 on NDM-1 was studied by site mutation, SPR, and zinc supplementation assays. Results PHT427 was identified as an inhibitor of NDM-1. It could significantly inhibit the activity of NDM-1 with an IC50 of 1.42 μmol/L, and restored the susceptibility of meropenem against E. coli BL21(DE3)/pET30a(+)-blaNDM–1 and K. pneumoniae clinical strain C1928 (producing NDM-1) in vitro. The mechanism study indicated that PHT427 could act on the zinc ions at the active site of NDM-1 and the catalytic key amino acid residues simultaneously. The mutation of Asn220 and Gln123 abolished the affinity of NDM-1 by PHT427 via SPR assay. Discussion This is the first report that PHT427 is a promising lead compound against carbapenem-resistant bacteria and it merits chemical optimization for drug development.